Effectiveness of training on health care workers' knowledge, attitude and practice regarding COVID-19 infection prevention and control, Yemen, 2021 - Abdulkareem Ali Hussein Nassar; Abdulwahed Abduljabar Al Serouri; Ahmed Hamod Al-Shahethi; Khaled Abdullah Almoayed (BMC, 2024)
Abstract Background Although several training courses for Health Care Workers (HCWs) on COVID-19 were conducted in Yemen, no evaluation has been done to assess the effectiveness of such training on the Knowledge, Attitude and Practice (KAP) of HCWs. Therefore, this study aimed to assess the effectiveness of training on the KAP of HCWs toward infection prevention and control (IPC) for COVID-19, determine the relationship between the change in the KAP of HCWs, and identify the associated factors with the change in KAP. Methodology A cross-sectional study was conducted from April to December 2021. It was conducted among 186 HCWs working at COVID-19 isolation centers and caring for COVID-19 patients, in all Yemen's governorates. The data were collected one week before and immediately after the training session. SPSS version 26 was used for data entry and analysis. The median, interquartile range (IQR) and median difference were calculated. The Wilcoxon Signed Ranks Test was used to estimate the significant difference between KAP pre- and post-training scores. Kurskal-Wallis and Mann-Whitney U tests were used to assess the associated factors. Spearman's correlation coefficient test was used to assess the statistical relationship between the change in KAP. A P value < 0.05 was considered statistically significant. Results Out of 186 HCWs, 181 HCWs filled the pre- and post-assessment, with a response rate of 97.3%. The median difference (IQR) in the KAP scores were 3.0 (1.0 and 6.0), 1.0 (-1.0 and 4.0) and 2.0 (-1.0 and 5.0), respectively. However, there are statistical difference in the KAP scores between the pre- and post-training (p value = 0.000, 0.004 and 0.000, respectively). There are significant positive correlations between the change in knowledge, attitude and practice (all p values < 0.01). A significantly change in knowledge was found among those working in epidemiological surveillance (p value = 0.031). Conclusions This evaluation concludes that the training program is effective in improving the KAP of HCWs toward IPC for COVID-19. It provides scientific evidence about the importance of training courses for HCWs during the COVID-19 pandemic. Further study is recommended to evaluate the retention of the KAP after a period of training.